The impact of menstrual phases on anaerobic power performance in collegiate women - Masterson, G. (The Journal of Strength and Conditioning Research, 1999)
The purpose of this study was to explore the impact of the menstrual phases on power performance in fairly active collegiate women. After the initial screening of 100 potential subjects who engaged in exercise 2 and no more than 3 days a week for 30 minutes or less, 32 subjects were selected to completed the study. The subjects underwent 2 Wingate tests to estimate anaerobic power, anaerobic capacity, and fatigue. One test was administered during the follicular phase; the other test was administered during the luteal phase. The data from this study indicate that there are differences between power performance during the follicular and luteal phases for these women. The women in this study demonstrated greater anaerobic capacity, produced greater peak power, and were less fatigued by the end of the exercise during the luteal phase than during the follicular phase. The results indicate that menstrual phase in fairly active collegiate women can have an influence on anaerobic performance.